Prediction model of surface roughness parameters of structural steel created by plasma arc cutting via full factor experiment. Issue 10 (5th August 2019) - Duplák, J.; Hatala, M.; Dupláková, D.; Botko, F.
Abstract: This article is focused on the prediction model of surface roughness parameters of structural steel created by plasma arc cutting. Optimization of the cutting process is very important from both quality and economy point of view. The presented paper shows the carrying out of the experiment with the specification of the design of experiments method. In these experiments, the influence of three factors ‐ the plasma current, the traverse speed, and plasma gas pressure was observed. Experimental material was selected structural steel S355. Along with the influence of controllable process factors was observed the influence of different plasma gasses. Application of different plasma gas significantly changes surface quality. The result of each experiment series is a regression function that can predict the Rz values according to the process parameters at given intervals. Presented equations can be applied in the production process for adjusting the plasma cutting process in order to achieve required surface quality.